TINJAUAN HUKUM EKONOMI SYARIAH TENTANG PENGEMBANGAN KAWASAN INDUSTRI PARIWISATA HALAL DI JAWA BARAT - Mutmainah, Naeli; Ahyani, Hisam; Putra, Haris Maiza (Universitas Islam Indonesia, 2022)
This article aims to uncover and explore: 1) Prospects of developing a halal tourism industrial area in West Java; 2) Review of sharia economic law in the development of the halal tourism industrial area in West Java. The legal research method used is normative legal research, including statutory regulations in the form of the Tourism Law, Minister of Tourism Regulations, Governor Regulations, Regional Regulations, and the MUI Fatwa on the Implementation of Halal Tourism. The legal research approach used in this study, namely the library research approach obtained from various library sources such as journals, the internet, books, and other documents relevant to Islamic business ethics, in the development of the halal tourism industrial area in Java. West. The theory used in this research uses the Maqashid Syariah theory and Islamic business ethics. The results of the study show that: 1) the prospect of developing a halal tourism industrial area in West Java has several development prospects in several aspects, in Bandung City and Bandung Regency developing Muslim-friendly tourism where the implementation is through the development of Halal Tourism Destinations in a more progressive, directed, and sustainable manner, in Ciamis Regency developed the concept of superior tourism by prioritizing excellent service and increasing professional and sustainable tourism potential, meanwhile in Pangandaran Regency developing a tourism concept which includes 5A (attractions, accessibility, amenities, available packages, activities, ancillary services) namely attractions, accessibility, facilities, available packages, activities, additional services. 2) Thus the review of sharia economic law in the development of the halal tourism industrial area in West Java is included in the recommended tourism concept, this is because the majority of the population is Muslim, in addition to maqashid sharia and Islamic business ethics that the concept of halal tourism in West Java including the concept of complementary tourism that prioritizes Islamic services in the implementation of its business, this can be seen from the availability of halal food, places of worship, and hotels that provide various needs of Muslim tourists. Artikel ini bertujuan untuk menguak serta menggali tentang : 1) Prospek Pengembangan kawasan industri pariwisata halal di Jawa Barat; 2) Tinjauan hukum ekonomi syariah dalam pengembangan kawasan industri pariwisata halal di Jawa Barat. Metode penelitian hukum yang digunakan adalah penelitian hukum normatif, meliputi peraturan perundang-undangan berupa UU Kepariwisataan, Peraturan Menteri Pariwisata, Peraturan Gubernur, Peraturan Daerah, dan Fatwa MUI tentang Penyelenggaraan Pariwisata Halal. Adapun pendekatan penelitian hukum digunakan dalam penelitian ini, yakni pendekatan penelitian kepustakaan (library research) yang diperoleh dari berbagai sumber kepustakaan seperti jurnal, internet, buku-buku, dan dokumen lainnya yang relevan tentang etika binsis islam, dalam pengembangan kawasan indutri pariwisata halal di Jawa Barat. Adapun teori yang digunakan dalam peneliti ini menggunakan teori Maqashid Syariah dan etika bisnis islami. Hasil penelitian menunjukkan bahwa : 1) prospek pengembangan kawasan industri pariwisata halal di Jawa Barat memiliki beberapa prospek pengembangan dalam beberapa aspek, di Kota Bandung dan Kabupaten Bandung mengembangkan wisata ramah muslim dimana pelaksanaannya melalui pengembangan Destinasi Pariwisata Halal secara lebih progresif, terarah, dan berkesinambungan, di Kabupaten Ciamis mengembangkan konsep pariwisata unggulan dengan mengedepankan pelayanan prima dan meningkatnya potensi kepariwisataan yang profesional dan kesinambungan, sementara itu di Kabupaten Pangandaran mengembangkan konsep pariwisata yang meliputi 5A (attractions, accessibility, amenities, available packages, activities, ancillary services) yakni atraksi, aksesibilitas, fasilitas, paket yang tersedia, aktivitas, layanan tambahan. 2) Dengan demikian tinjauan hukum ekonomi syariah dalam pengembangan kawasan industri pariwisata halal di Jawa Barat termasuk pada konsep pariwisata yang dianjurkan, hal ini dikarenakan mayoritas penduduknya adalah muslim, selain itu secara maqashid syariah dan etika bisnis islami bahwa konsep pariwisata halal yang ada di Jawa Barat termasuk pada konsep pariwisata pelengkap yang mengedepankan pelayanan islami dalam pelaksanaan bisnisnya, hal ini dapat dilihat dari tersedianya makanan halal, tempat ibadah, dan hotel-hotel yang menyediakan berbagai kebutuhan wisatawan muslim.